Strategi Kreatif Program K-Hits MNC Music dalam Mengemas Konten K-Pop - Ryan Windy Pratama; Altobeli Lobodally (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2026)
Korean pop has come up with many creative ideas for a number of communication products, one of which is television program programs. K-Hits is a television program that packages K-Pop content produced by MNC vision and aired on channel 111. K-Hits discusses music, series, dramas, and information about South Korean idols. This research aims to describe the creative strategies used by K-Hits in packaging K-Pop content. A descriptive qualitative approach with a case study method and a post-positivism paradigm is used in this study. The format of the event, artistic arrangement, and the choice of music and fashion became the main creative strategies in the production of K-Hits programs while gimmicks became supporters for the creation of a festive atmosphere. However, researchers found that punching lines have not been used so this element needs to be implemented so that viewers do not feel bored when watching K-Hits programs because there is a surprise effect in the TV program.